The association between circulating palmitic acid levels and risk of premature coronary artery disease in Chinese patients: a case-control study - Yingwen Chen; Yue Cao; Lingxiao Li; Peng Chen; Xiaomei Zhang; Shali Hao; Min Qiu; Yangguang Liu; Jiandi Wu; Yangxin Chen; Zaopeng He; Yunzhao Hu; et al. (BMC Cardiovascular Disorders)
Abstract Background Palmitic acid (PA) is a risk factor for atherosclerosis but its significance in premature coronary artery disease (PCAD) remains poorly understood. Herein, we investigated the impact of circulating PA levels on the risk of PCAD occurrence in Chinese patients. Methods In this case control study, we included patients diagnosed with PCAD and age-matched non-CAD controls between June 2022 and December 2023. Participants’ serum PA levels were quantified using ultra-performance liquid chromatography-mass spectrometry, and correlations with PCAD were determined using R (v4.2.2). The potential mediating effect of low density lipoprotein cholesterol (LDL-C) for the association between PA and PACD was also evaluated. Results In this study of 393 adults (206 PCAD patients and 187 non-CAD controls), serum PA levels showed significant positive correlations with LDL-C and total cholesterol. Compared to controls, PCAD patients had higher proportions of males, smokers, and diabetics, along with elevated PA, LDL-C, and triglycerides, but reduced HDL-C (all P < 0.05). Elevated serum PA (per 10µmol/L increase, OR = 1.12, 95% CI = 1.05–1.20) was significantly associated with an increased risk of PCAD after adjustment for multivariable factors. Further adjustment for LDL-C levels attenuated, but remained statistically significant, the association between PA and PCAD (per 10µmol/L increase, OR = 1.10, 95% CI = 1.03–1.18). Mediation analysis showed that LDL-C mediated 16% of PA’s total effect on PCAD. Conclusions Elevated PA circulating levels were found to be related with PCAD risks among Chinese, and increased LDL-C levels could partly mediate this effect.